Éléments institutionnalistes pour la mise en perspective historique du concept de monnaie endogène - Thibault Laurentjoye; Léo Malherbe (Revue de la Régulation)
The purpose of this article is to make a contribution to the debates surrounding the endogeneity of money, inspired by institutionalist thinking. After recalling the main elements of endogenous money theory and the context of its emergence among post-Keynesians, we will pay particular attention to the controversy between the proponents of so-called « evolutionary » endogeneity and the supporters of so-called « revolutionary » endogeneity. The stumbling block between these two approaches pertains to the historical dimension of the concept of endogenous money. In other words, it is a question of whether, over the course of history, the quantity of money has always adjusted endogenously to changes in demand. We suggest that to answer this question, the endogeneity of money should be considered by considering two dimensions of analysis. A first dimension regards time, separating long time (that of institutional change) from short time (that of macroeconomic adjustments). For each of these temporalities we then distinguish the endogeneity at the level of monetary instruments from the analysis of endogeneity at the level of the monetary system. The adjustment of supply to demand in the short term must take into account the diversity of the monetary instruments that constitute the monetary system under study; while endogeneity in the long term refers to the evolution of the relative weight of monetary instruments within the system.